Diagnosis and Management of Brain Tumors in Children - Taslim S. Soetomenggolo; Hardiono Pusponegoro; Jimmy Passat; Dwi Putro Widodo; Sofyan Ismael (Paediatrica Indonesiana, 1995)
Brain tumors are the second most common malignancy and the most common solid tumors found in childhood. During 11 months 19 patients with brain tumors were hospitalized at the Department of Child Health, Dr. Cipto Mangunkusurno Hospital, Jakarta, 10 of them were males. The youngest patient was 5 months old and the oldest was 13 years old. The important signs and symptoms in establishing diagnosis were the non-localizing signs and symptoms, i.e., nausea and vomiting. The most frequent localizing signs and symptoms were papilledema, cranial nerves palsy, ataxia and incoordination, hemiparesis, visual disturbances, and optic atrophy. Focal seizures were rare. Most of the tumors were in infratentorial region, and metastatic tumors were rare. The mortality of this series was high due to the severity of the disease. The most frequent of tumors are astrocytomas and medulloblastomas.